PROFIL KEMAMPUAN KOGNITIF SISWA SMA DALAM PEMBELAJARAN FISIKA MENGGUNAKAN TEKNIK PEMBELAJARAN ‘TAKE-AWAY’ - Ria Trisnia Naufalina; Irma Rahma Suwarma; Asep Sutiadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The title of this research is "Profile of Cognitive Abilities on students’ High School in Learning Physics with Take-Away Technique''. The purpose of the Take-Away Techniqueis to develop the students’ attitude and ability for taking the core of learning. The use of the Take-Away Technique expected to appear the sense of responsibility of students to conduct independent learning either before or after learned in school. The purpose of this study was to determine how the profile of cognitive abilities on students’ High School before and after using the Take-Away Technique. The research used Pre-Experimental methode and  One-group pretest-posttest design. The Take-Away Technique applied in one of high school in Tasikmalaya city with 33 students. The research instrument is a test to measure students' cognitive abilities in the sphere of C2 (understand), C3 (apply) and C4 (analyze), essay test and assesment rubric. The results of this study indicate that students 'cognitive abilities before applying the Take-Away Technique are still low, only 9% of students who received grades above KKM (minimal completeness criteria), while after applying the Take-Away Technique student’s cognitive abilities increased by 63% of students who received grades above KKM (minimial completness criteria). Therefore, there are differences in the profile of students' cognitive abilities before and after applied the Take-Awat Technique.Keywords:  "Take-Away" Technique, cognitive ability, ability for taking the core of learning, responsibility, independent learning